Timing of Optimal Surgical Intervention for Neonates with Necrotizing Enterocolitis. Issue 5 (May 2015) - Munaco, Anthony J.; Veenstra, Michellea; Brownie, Evan; Danielson, Logan A.; Nagappala, Kartheek B.; Klein, Michael D.
Up to half of all patients with necrotizing enterocolitis require acute surgical treatment. Determining when to operate on these patients can be challenging. Utilizing a combination of clinical and metabolic indicators, we sought to identify the optimal timing of surgical intervention. A retrospective chart review was conducted on patients with necrotizing enterocolitis from 2001 to 2010. Previously validated clinical (abdominal erythema, palpable abdominal mass, hypotension), radiographic (pneumoperitoneum, portal venous gas, fixed bowel loop, severe pneumatosis intestinalis), and laboratory (acidosis, bacteremia, hyponatremia, bandemia, neutropenia, thrombocytopenia) indicators were assessed for the ability to predict the need for acute surgical intervention as a simple indicator score, based on the sum of the indicators listed above. A total of 197 patients were included. One hundred and twenty-four procedures (28 peritoneal drains, 96 laparotomy) were performed on 122 patients (62%). Median indicator score was 4 (range: 0–8). Logistic regression identified abdominal erythema (odds ratio [OR] = 3.3, P = 0.001), acidosis (OR = 2.6, P = 0.004), and hypotension (OR = 1.9, P = 0.05) as independently associated with surgical intervention. A significant increase in surgical intervention was noted for patients with indicator score of 3 or more. In conclusion, if three or more indicators exist, operative intervention is very likely required. In the absence of pneumoperitoneum, abdominal erythema, acidosis, and hypotension are especially important.